Influence of temperature and binder content on the properties of a sintered product based on red mud - Krgović, Milun (Materiali in tehnologije, 2014)
In this paper we present an investigation into the properties of a sintered product based on red mud with respect to the sintering temperature and the binder content (illite-kaolinite clay). In the Bayer process for obtaining alumina, red mud is a by-product (solid waste from the leaching of bauxite). Using red mud as a raw material mixture component to obtain sintered products, a cheap raw material for construction and ceramics would be obtained, and the environmental problems resulting from the frequent deposits of red mud in pools would be solved. Based on the overall results of our examinations in this study, it can be concluded that the change of basic parameters, sintering temperature and binder content (illite-kaolinite clay), can provide satisfactory characteristics for the sintered product in terms of mechanical properties, volume shrinkage during sintering and total porosity.
Keywords: rdeče blato; red mud; clay; glina; porosity; poroznost; compressive strength; tlačna trdnost